Analysis of the Effectiveness of the Use of E-Parking System in the Payment of Parking Fees in Jember District - Asila Ulin Nuha Asila; Thoriq Al Thof; Siti Indah Purwaning (Medikun Publisher, 2024)
Rapid population growth and increasing demand for private vehicles make parking problems one of the biggest challenges for local governments. Jember Regency, one of the urban areas in Indonesia, is not spared from this complex parking problem. This study uses a qualitative approach to analyze the effectiveness of the use of e-parking system in paying parking fees in Jember Regency. Data collection methods include interviews, documentation, and observation. The purpose of this research is to identify the advantages and disadvantages of the e-parking system, compare the effectiveness of using the e-parking system with conventional methods, and identify factors that affect the effectiveness of using the e-parking system. The results of this study are expected to contribute knowledge and insights, as well as provide recommendations for the improvement and development of the e-parking system. The e-parking system offers ease of access, payment, and management of parking spaces, but also has drawbacks such as dependence on technology. Factors that affect the effectiveness of e-parking systems include human resource training, public response, illegal parking, and education. Comparison with conventional methods is also the main focus of this research